Comprehensive prevention strategies for retinopathy of prematurity: a literature review - Zeng Zi (Sciendo, 2023)
Retinopathy of prematurity (ROP) is a kind of disease that can be seen in premature infants. It may cause a series of short- and long-term complications such as poor vision in premature infants, causing irreversible damage to them. Therefore, if we can prevent this disease, we can solve the above problems. This study summarized some factors that influence ROP, such as low gestational age, low birth weight, irrational oxygen use, anemia, blood transfusion, and thrombocytopenia; and also summarized a series of interventions that can prevent or delay the progression of ROP, such as reducing blood transfusion, the application of antenatal corticosteroids, and delaying clip umbilical cord, which can provide some reference for better clinical practice of preventing ROP.